2010
DOI: 10.1007/s11064-010-0310-4
|View full text |Cite
|
Sign up to set email alerts
|

Phenylarsine Oxide Binding Reveals Redox-Active and Potential Regulatory Vicinal Thiols on the Catalytic Subunit of Protein Phosphatase 2A

Abstract: Our earlier finding that the activity of protein phosphatase 2A from rat brain is inhibited by micromolar concentrations of the dithiol cross-linking reagent phenylarsine oxide (PAO) has encouraged the hypothesis that the catalytic subunit (PP2Ac) of PP2A contains one or more pairs of closely-spaced (vicinal) thiol pairs that may contribute to regulation of the enzyme. The results of the present study demonstrate using immobilized PAO-affinity chromatography that PP2Ac from rat brain formed stable DTT-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Most of these proteins, including DPYL2, RhoGDI, CapZ beta, PP2A-alpha, UCHL1, HSC71 and enolase, are prone to oxidative modifications. [60][61][62][63] If anatomical alterations clearly indicate damage caused by oxidative stress in neuronal circuits, they are not necessarily causally linked to behavioral alterations, although they may contribute to them. 64 Although oxidative stress are mostly in neurons, there were also indications of oxidative stress in some glial cells in V animals.…”
Section: Upstream Regulation Of Nrf2mentioning
confidence: 99%
“…Most of these proteins, including DPYL2, RhoGDI, CapZ beta, PP2A-alpha, UCHL1, HSC71 and enolase, are prone to oxidative modifications. [60][61][62][63] If anatomical alterations clearly indicate damage caused by oxidative stress in neuronal circuits, they are not necessarily causally linked to behavioral alterations, although they may contribute to them. 64 Although oxidative stress are mostly in neurons, there were also indications of oxidative stress in some glial cells in V animals.…”
Section: Upstream Regulation Of Nrf2mentioning
confidence: 99%
“…For comparison, only 4-6% of total proteins from whole brains were found to contain disulfide bonds under these (Foley et al, unpublished observation) and comparable conditions (Foley et al 2010(Foley et al , 2011. Furthermore, it is important to note that our previous findings that the extracellular protein albumin, which contains 17 disulfide bonds, is one of two proteins found to be highly enriched among the disulfide bond-containing proteins argues that the fraction of intracellular proteins exhibiting intrachain disulfide bonds in vivo is likely to be substantially lower than the 4-6% value (Foley et al 2010).…”
Section: Discussionmentioning
confidence: 94%
“…2), may undergo reversible oxidation to form disulfide bonds was examined following preparation of these fractions in the absence of reducing agents and subsequent alkylation of reduced protein thiols with iodoacetamide. We have shown previously that the omission of reducing agents is sufficient to promote disulfide bond formation in proteins during subcellular fractionation procedures even when carried out 4°C and in the presence of 1 mM EDTA (Foley et al 2011).…”
Section: Snap-25 Forms Intrachain Disulfide Bondsmentioning
confidence: 99%
“…Evidence has also been reported that PP2A phosphatase activity is sensitive to oxidative stress,42 and this sensitivity is proposed to be mediated by oxidation of a pair of vicinal cysteines located near the phosphatase active site of the C subunit 43. Additionally, PP2A oxidation by exposure to micromolar levels of hydrogen peroxide has been shown to completely block its methylation by LCMT‐1 44.…”
Section: Discussionmentioning
confidence: 99%